A New Formulation of Calcitriol (DN-101) for High-Dose Pulse Administration in Prostate Cancer Therapy - Henner, William David (MedReviews, LLC, 2003)
Although the antineoplastic activity of calcitriol in prostate cancer has been known for many years, the agent’s use in oncology has been prevented because of the occurrence of hypercalcemia with daily administration. High-dose pulse administration of calcitriol has the potential to improve the therapeutic index of calcitriol. Results of a phase II study of calcitriol and docetaxel (Taxotere®) suggest that this combination may have utility in androgen-independent prostate cancer (AIPC). DN-101, a high-dose (15 μg) formulation of calcitriol suitable for use in oncology, is now being tested in a randomized trial (AIPC Study of Calcitriol Enhancing Taxotere). This formulation of calcitriol could become an important new tool for improving the efficacy of docetaxel in the treatment of AIPC and would join the ranks of other nuclear receptor ligands in cancer treatment. Investigations of DN-101 in the treatment of a broad range of tumor types and in combination with a variety of agents are an exciting new area of research.